1992
DOI: 10.1016/0042-6822(92)90757-g
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infects and causes demyelination in primate central nervous system

Abstract: Two species of primates, Owl and African green monkeys, were inoculated intracerebrally with either the neurotropic mouse hepatitis virus JHM or the putative multiple sclerosis brain coronavirus isolate SD. These viruses caused an acute to subacute panencephalitis and/or demyelination in the infected animals. The course of pathogenesis and sites of detected viral RNA and antigen was dependent both on animal species and virus strain but the results clearly showed that these viruses replicated and disseminated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 38 publications
1
81
0
Order By: Relevance
“…Some murine coronaviruses are neurotropic, neuroinvasive, and neurovirulent in rodents (27,58) and in nonhuman primates (11,38), inducing in some cases an MS-like demyelinating disease. Our goal is to investigate the possible neurotropism, neuroinvasion, and neurovirulence of the related HCoV, which have so far only been definitively associated with respiratory infections, with occasional reports of associations with diarrhea and neurologic diseases, mainly MS (39).…”
Section: Discussionmentioning
confidence: 99%
“…Some murine coronaviruses are neurotropic, neuroinvasive, and neurovirulent in rodents (27,58) and in nonhuman primates (11,38), inducing in some cases an MS-like demyelinating disease. Our goal is to investigate the possible neurotropism, neuroinvasion, and neurovirulence of the related HCoV, which have so far only been definitively associated with respiratory infections, with occasional reports of associations with diarrhea and neurologic diseases, mainly MS (39).…”
Section: Discussionmentioning
confidence: 99%
“…12,18,24 Primers used for amplification were as follows: complementary DNA (cDNA) synthesis (R1) 5Ј-ACGGACACCCAAAGTA-3Ј, upstream primer (R2) 5Ј-AGCACTTCTGTTTCCC-3Ј for picornavirus 25 ; cDNA synthesis (FAM1) 5Ј-CAGAGACTTGAAGATGTCTTTGC-3Ј, upstream primer (FAM2) 5Ј-GCTCTGTCCATGTTATTTG (GA)AT-3Ј for influenza virus type A 26,27 ; and cDNA synthesis (CVP3) 5Ј-IIAAATTGCTIITCTTGTTCTGGC-3Ј (I indicates inosine), downstream primer (CVP4) 5Ј-CCAAAATTCTGATTAGGGCCTCTC-3Ј for coronavirus OC43. 28 Complementary DNA was synthesized for 1 hour at 43°C in a reaction mix containing 10-mmol/L tromethamine hydrochloride (pH, . After an initial 4-minute heat denaturation at 94°C, 40 cycles of heat denaturation at 94°C for 1 minute, primer annealing at 49°C (picornavirus), 55°C (influenza virus type A), or 58°C (coronavirus) for 1 minute 30 seconds, and primer extension at 72°C for 1 minute were followed by a final primer extension step at 72°C.…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…In this study we demonstrated that JHM virus estab-in mice, MHV persistent infections have also been detected in the rat and monkey CNS (27,28). lished a persistent infection within the retina of BALB/ c mice.…”
mentioning
confidence: 62%